Combining textured insoles and compelled body weight shift improves lower limb function and gait in individuals with stroke: a randomised controlled trial - Ahmad, Adamu Adamu; Suriyaamarit, Duangporn; Siriphorn, Akkradate (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Purpose. To assess the effects of combining textured insoles (TI; plantar somatosensory stimulation) with compelled body weight shift (CBWS) on lower limb motor function, gait, and sensory function in stroke patients.Methods. This randomised controlled trial included 60 stroke patients allocated into four groups, including control, CBWS, TI, and CBWS+TI (combined). Each group participated in an eight-week intervention, with outcome measures comprising the Fugl-Meyer Assessment of the Lower Extremities for motor function, Semmes-Weinstein Monofilaments test for sensory function, Gait Assessment and Intervention Tool for overall gait quality, 10-Metre Walk Test (10MWT) for gait speed, and Timed Up and Go (TUG) test for functional mobility.Results. Lower limb motor function exhibited enhancement in the control, TI, and Combined groups, with the most significant improvement observed in the combined group. The enhancement of sensory function only occurred in the combined group. The gait quality improved in all groups, but there were no significant differences between them. Gait velocity increased sub-stantially in the control and CBWS groups, while TUG time decreased in both.Conclusions. Combining plantar somatosensory stimulation and CBWS improved lower limb motor and sensory function in stroke patients but did not enhance gait speed or mobility beyond individual interventions.
Keywords: gait disorders; motor activity; rehabilitation; sensation; weight-bearing